Controlling overhead in public sector organizations. Issue 6 (5th August 2014) - Van Helden, G.J.; Huijben, Mark
Abstract : Purpose: – The purpose of this paper is to explore various mechanisms for controlling overhead, as informed by a framework based on transaction-cost-economics (TCE). Design/methodology/approach: – Development of framework for controlling overhead and field study about Dutch public sector organizations for exploring and enriching this framework. Findings: – Central steering with a provider-user interface was often seen as the most desirable control mechanism. Although central steering without such interface was used in about half of the overhead functions, their users argued that the priorities of these functions were insufficiently in line with their needs. There was little support for internal market control, because it would increase the administrative workload of internal calculations, and it could lead to undesirable differences in overhead use among the primary services departments. Moreover, line managers are often more focused service quality than costs. Research limitations/implications: – The framework based on TCE formed a suitable starting point for reflecting on the control of overhead functions, but the empirical findings pointed to revisions in the case of internal market control concerning resistance to administrative workload and avoidance of differences in the supply of internal services. Practical implications: – Inspiring public sector managers to reflect on the match between overhead control mechanisms and characteristics of overhead functions. Originality/value: – A theoretical underpinning and empirical exploration of a variety of overhead control mechanisms in the public sector.